2022
DOI: 10.3390/jof8020174
|View full text |Cite
|
Sign up to set email alerts
|

A Fungal Defensin Inhibiting Bacterial Cell-Wall Biosynthesis with Non-Hemolysis and Serum Stability

Abstract: Defensins are a class of cationic disulfide-bridged antimicrobial peptides (AMPs) present in many eukaryotic organisms and even in bacteria. They primarily include two distinct but evolutionarily related superfamilies (cis and trans). Defensins in fungi belong to the members of the cis-superfamily with the cysteine-stabilized α-helical and β-sheet fold. To date, many fungal defensin-like peptides (fDLPs) have been found through gene mining of the genome resource, but only a few have been experimentally charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The stability of AMPs is an important prerequisite for their effectiveness in vivo [ 26 , 27 ]. Thus, we evaluated the changes of antibacterial activity of Pleu and its modified peptides at different temperatures (40 to 121 °C) and pH (2 to 12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of AMPs is an important prerequisite for their effectiveness in vivo [ 26 , 27 ]. Thus, we evaluated the changes of antibacterial activity of Pleu and its modified peptides at different temperatures (40 to 121 °C) and pH (2 to 12).…”
Section: Resultsmentioning
confidence: 99%
“…We found that monovalent cations had little effect on the antibacterial activity of peptides, while divalent cations greatly weakened the activity of Pleu and its modified peptides ( Table 3 ). Furthermore, the media containing 10% fetal bovine serum, plasma and DMEM were used to simulate the matrix environment in vivo [ 27 ]. The results showed that these three substances would not weaken the antibacterial activity of the compounds we tested.…”
Section: Resultsmentioning
confidence: 99%
“…It is isolated from fermented foods, and has been also been isolated among animals, e.g. in dogs, cats, goats, horses, monkeys, pigs, rodents and sheep, as well as in fish food [2,16,17,18,19,20,21]. In humans, the most common sites of isolation are the skin of the lower limbs, arms, head and nostrils.…”
Section: Discussionmentioning
confidence: 99%
“…As long ago as 1891, the American pathologist William H. Welch, in his work 'Conditions underlying the infection of wounds', pointed out the obvious fact that bacteria are responsible for wound infection. He also described Staphylococcus epidermidis albus, a coagulase-negative staphylococcus, as a bacterium that almost constantly colonises human skin, but also presented it as a potential pathogen that could be responsible for wound infection [1,2]. With the continuous development of medicine, including the increasing use of invasive techniques, the importance of coagulasenegative staphylococci is increasing significantly [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Eukaryotes and bacteria can produce defensins. Defensins are a class of cysteine-rich AMPs with short, cationic disulfide bridges [ 54 ]. They can be grouped into two superfamilies (cis and trans) ( Figure 4 ).…”
Section: Antimicrobial Peptides’ Natural Sourcementioning
confidence: 99%